Ultrasonic vibration-assisted laser directed energy deposition in-situ synthesis of NiTi alloys: Effects on microstructure and mechanical properties. (December 2020) - Zhang, Dongzhe; Li, Yunze; Wang, Hui; Cong, Weilong
Abstract: Nickel-Titanium (NiTi) alloys have the unique shape memory effect and pseudoelasticity, good damping capacity, good corrosion resistance, and excellent biomechanical compatibility. These properties make NiTi alloys attractive in industries like automobile, aerospace, medical device, etc. However, it's difficult to fabricate and machine NiTi alloys due to their rapid work-hardening property and pseudoelasticity. Traditional manufacturing methods, such as casting and powder metallurgy, show disadvantages of high cost, time-consuming, and limitations in fabrication of parts with complex geometry. In order to reduce or solve these problems, laser additive manufacturing (LAM) methods have been applied for the fabrication of NiTi alloys. Among the LAM methods, laser directed energy deposition (DED) in-situ synthesis of NiTi alloys from the premixed Ni and Ti powders shows its unique advantages of cost-effectiveness and flexibility in altering NiTi alloys' phase transformation and mechanical properties. However, heterogeneous microstructures and the formation of secondary phases are two crucial issues that impede the application of laser DED to in-situ synthesis NiTi alloys. Ultrasonic vibration has pronounced effects on liquid materials solidification processes, which could be utilized in homogenizing the microstructure and reducing the secondary phase of laser DED in-situ synthesized NiTi alloys. This paper, for the first time, reports in-situ synthesis of NiTi alloys by laser DED with ultrasonic vibration assistance. The effects of ultrasonic vibration on microstructure properties (microstructure homogeneity, internal defects, elemental composition, grain size, and phase constituents) and mechanical properties (pseudoelasticity, microhardness, and Young's modulus) have been investigated.